Academic Self-Efficacy dan Motivasi Belajar: Studi pada Mahasiswa Rantau - Saidah, Tazkiya; Sugianto, Angelina Henias; Wahyuda, Intan Febriaputri (Universitas Trunojoyo Madura, 2025)
Learning motivation in regional students often decreases along with academic pressure and the demands of adapting to a new environment. In this context, academic self-efficacy is considered as an important psychological factor that has the potential to influence the level of learning motivation in students. This study aims to determine the relationship between academic self-efficacy and learning motivation in regional students of X University. This study used a quantitative approach with a correlational non-experimental design. This study involved 107 overseas students who were actively enrolled in X University, who came from the classes of 2022, 2023, and 2024, obtained through purposive sampling technique. The instruments used were The Academic Self-Efficacy Scale (TASES) and the Learning Motivation Scale which were validated and reliable. Data analysis performed using Pearson correlation. Based on the results of the study, a significant correlation was found between academic self-efficacy and learning motivation. These findings emphasize that strengthening academic self-efficacy and learning motivation simultaneously is very important to help overseas students cope with academic pressure. Based on the findings, it is recommended for regional students to increase academic self-efficacy and learning motivation. The implications of this study recommend the development of student's academic self-efficacy and learning motivation through the application of active learning strategies and the creation of an academic environment that optimally supports the learning process.